Penerapan Metode Akuntansi Keuangan Lanjutan 2 Dalam Meningkatkan Efisiensi Pengelolaan Keuangan Perusahaan - Muhammad Febriansyah; Dion Pramudana; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
This article discusses the application of the advanced 2 financial accounting method in Indonesia and the effect of implementing SAK-ETAP on its use, especially for small and medium entities. This method can improve the efficiency of the company's financial management, but also faces several challenges and constraints, especially for SMEs which are still limited in human and technological resources. To overcome this, SMEs can develop adequate human resources, utilize available technology, and follow the requirements and accounting principles set out in SAK-ETAP. Thus, SMEs can take advantage of the application of advanced financial accounting methods 2 and SAK-ETAP as a tool to improve financial management and overall business performance.